Severe Asthma: Challenges and Precision Approaches to Therapy. Issue 2 (December 2016) - Larsson, Kjell; Menzies-Gow, Andrew; Panettieri, Reynold
Abstract Current therapies are inadequate for patients with severe asthma. The development of biomarkers and novel targeted therapies should allow for the introduction of precision medicine for patients with severe asthma and the T2 high endotype. However, there remains a pressing need to better understand the underlying pathophysiology of T2 low asthma to help develop better biomarkers and better treatments for this group of patients. The emergence of biomarkers may serve value in characterizing airway disease and in devising precision approaches to address specific disease mechanisms. To date, biomarkers remain somewhat exploratory until further research can characterize the validity and reliability of these approaches in improving asthma care. Partnerships among providers, payers, and industry will enhance our ability to discover new approaches that target specific mechanisms and improve disease outcomes. Ultimately, our goals are to align phenotypes with endotypes to direct therapies that will provide the right intervention at the right time for the right person with the right diagnosis.